Intra-operative diagnosis of an adult ureterocele complicated by hydronephrosis: a case report - Ileri, Alper; Onur, Zeynep Yasemin; ozmus, Dogay Nurtac; atci dogdu, Irmak; Budak, Adnan; Ozmus, Duygu Cebecik; Baris, Pinar Tugce; Akpak, Yasam Kemal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ureterocele is a cystic dilatation of the terminal ureter. Hydronephrosis is less commonly reported in individuals with ureterocele. We report a unique case of an incidental ureterocele with hydronephrosis in a 47-year-old woman; diagnosed with intraoperative control cystoscopy while performing total laparoscopic hysterectomy and bilateral salpingo- oophorectomy.